ChemInform Abstract: Palladium Catalyzed C—H Bond Acetoxylation: Isoxazolinyl as a Directing Group. Issue 44 (13th October 2016) - Geng, Caiwei; Jiang, Minghui; Feng, Lifei; Jiao, Peng
Abstract: All yields are based on recovered starting material.